Peran Mediasi Komitmen Organisasional, Kepuasan Kerja: Pengaruh Iklim Organisasi Terhadap Kinerja Karyawan - Fakhrudin Rifai, Royyan; Setiawan, Fery (PROGRAM STUDI EKONOMI ISLAM PROGRAM PASCASARJANA IAIN SULTAN MAULANA HASANUDDIN BANTEN, 2023)
Every organization will always be required to be able to create a conducive organizational climate to achieve the expected quality of performance. To achieve this, good human resource management is required and of course also always paying attention to factors that can be influential in achieving maximum employee performance, in accordance with the goals set by the organization. The variables of job satisfaction and organizational commitment are often tested as mediating factors in the influence of organizational climate on employee performance. The aim of this research is to examine and analyze the mediating role of organizational commitment and job satisfaction in the influence of organizational climate on employee performance. This research used a cross sectional method with 78 respondents from PT employees. Hariqu Mulya Sejahtera is located in the city of Ponorogo, East Java. Once collected, the data is processed and analyzed with the help of Smartpls 4.0 software. The research results show that (1) organizational commitment does not mediate the influence of organizational climate on employee performance (2) Job satisfaction mediates the influence of organizational climate on employee performance